Stereotactic Body Radiation Therapy for Low- to Intermediaterisk Prostate Adenocarcinoma - 정배권; 정기현; 정호진; 하인봉; 최훈식; 남성철; 화정석; 현재석; 최시민; 강기문 (Journal of Korean medical science, 2015)
The aim of the present study was to evaluate the efficacy and toxicity of stereotactic body radiation therapy (SBRT) for low- to intermediate-risk prostate adenocarcinoma. Thirtynine patients were retrospectively reviewed. The SBRT was delivered using the CyberKnife with the fiducial tracking method combined with In-tempo imaging. The gross target volume, which included the prostate only, was delineated on the fused CT/MRI scans. The prescription dose was delivered every other day as 5 fractions of 7.5 Gy. Venous blood was obtained before and after SBRT to assess the prostate-specific antigen (PSA) level. Toxicity was evaluated using the CTCAE, v4.03. The median follow-up time was 30.0 months. The median initial PSA level was 7.7 ng/mL. PSA levels decreased in all patients treated with SBRT, and after 5 months, the median PSA was less than 2 ng/mL. The rate of overall 3-yr actuarial biochemical failure free survival was 93.9%. Acute side effects were generally comparable with those of previous studies. The PSA change and toxicity after SBRT for low- to intermediate-risk prostate adenocarcinoma indicates favorable biochemical responses and tolerable levels of toxicity. Additionally short course treatment may produce cost benefit and convenience to patients. KCI Citation Count: 0